2010
DOI: 10.1002/ppul.21149
|View full text |Cite
|
Sign up to set email alerts
|

Acid steatocrit determination is not helpful in cystic fibrosis patients without or with mild steatorrhea

Abstract: AS does not reflect in a reliable way FFE in CF patients without or mild steatorrhea. Its applicability in the assessment of FFC in such patients has therefore limited practical value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Qualitative fecal fat ("spot fecal fat") is not recommended due to its lack of specificity since a high fat intake in a normal patient can lead to a false positive result and diets rich in calcium can lead to increased fecal fat excretion [24]. The acid steatocrit has similar limitations and was shown to be less accurate than fecal fat excretion studies [25].…”
Section: Indirect Testsmentioning
confidence: 99%
“…Qualitative fecal fat ("spot fecal fat") is not recommended due to its lack of specificity since a high fat intake in a normal patient can lead to a false positive result and diets rich in calcium can lead to increased fecal fat excretion [24]. The acid steatocrit has similar limitations and was shown to be less accurate than fecal fat excretion studies [25].…”
Section: Indirect Testsmentioning
confidence: 99%
“…In our study, 65% of infants aged 1 to 3 months had FFC higher (median 6.3%) than normal values proposed by other groups (<5% for children). On the other hand, FFE in this group was higher than 4 g/day only in 2 children, while the applied cutoff level refers to subjects older than 2 years (1,15). It should be noted that the available data, however, are remarkably insufficient and contradictory.…”
Section: Discussionmentioning
confidence: 94%
“…6 In contrast, Wagner et al 50 did not find a strong correlation between AS and CFA. Walkowiak and colleagues 51 studied the use of AS compared with fecal fat excretion (the inverse of CFA) in pwCF being treated with PERT and concluded that its applicability in the assessment of fecal fat content in this subgroup of patients has limited practical value; this article is an excellent review of the AS literature.…”
Section: Sparse Stoolmentioning
confidence: 99%